Healthy dietary patterns decrease the risk of colorectal cancer in the Mecca Region, Saudi Arabia: a case-control study - Firas S. Azzeh; Eyad M. Alshammari; Awfa Y. Alazzeh; Abdelelah S. Jazar; Ibrahim R. Dabbour; Hani A. El-Taani; Ahmed A. Obeidat; Fayrooz A. Kattan; Sufyan H. Tashtoush (BMC, 2017)
Abstract Background Colorectal cancer (CRC) is the first most common cancer in males and the third most common cancer in females in Saudi Arabia. Dietary habits are strongly associated with the inhibition or proliferation of malignancy. Therefore, this study is aiming to investigate the risks and protective benefits of dietary factors affecting CRC in the Mecca region of Saudi Arabia. Methods A case-control study was conducted from June 2014 to March 2015. One hundred thirty-seven patients with colon and/or rectal cancer were recruited in the case group, while 164 healthy participants were recruited in the control group. A questionnaire was completed with the help of trained dietitians to study the effects of several dietary patterns on the risk of CRC. Results Dairy product intake of 1-5 servings/day, legume intake of 3-5 servings/week, leafy vegetables intake of 1-5 servings/week, olive oil intake of 1-5 servings/week, black tea intake of three or more cups/day, and coffee intake of one or more cups/day was found to decrease the risk of CRC in participants. Conclusion This study highlights the importance of changing dietary habits to decrease CRC incidence in the Mecca region.